2015
DOI: 10.1007/s10295-015-1624-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of l-sorbose in an industrial Gluconobacter oxydans strain by identification of a strong promoter based on proteomics analysis

Abstract: Gluconobacter oxydans is capable of rapidly incomplete oxidation of many sugars and alcohols, which means the strain has great potential for industrial purposes. Strong promoters are one of the essential factors that can improve strain performance by overexpression of specific genes. In this study, a pipeline for screening strong promoters by proteomics analysis was established. Based on the procedure, a new strong promoter designated as P B932_2000 was identified in G. oxydans WSH-003. The promoter region was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Studies have shown that strong promoters are usually obtained from the promoters of essential genes whose transcription levels are presumed to be high and constant [17]. In addition, we found that some commonly-used strong promoters such as P dnak in Gluconobacter oxydans and P gro in Corynebacterium glutamicum are promoters of molecular chaperones [18,19]. In this study, the promoters for 20 genes with high transcription levels and 6 molecular chaperone-encoding genes are identified by bioinformatic methods and their activities were further examined experimentally.…”
Section: Introductionmentioning
confidence: 80%
“…Studies have shown that strong promoters are usually obtained from the promoters of essential genes whose transcription levels are presumed to be high and constant [17]. In addition, we found that some commonly-used strong promoters such as P dnak in Gluconobacter oxydans and P gro in Corynebacterium glutamicum are promoters of molecular chaperones [18,19]. In this study, the promoters for 20 genes with high transcription levels and 6 molecular chaperone-encoding genes are identified by bioinformatic methods and their activities were further examined experimentally.…”
Section: Introductionmentioning
confidence: 80%
“…The bioconversion of D-sorbitol to L-sorbose by Gluconobacter oxydans is catalyzed by D-sorbitol dehydrogenase, encoded by the sldh gene. Increased expression of this gene resulted in increased bioconversion activity (Hu et al, 2015). The sorbose concentration was increased to 144 g/L at 16 hours.…”
Section: Additional Applications Of Microbial Enzymesmentioning
confidence: 99%
“…A large number of promoters have previously been used successfully to improve product yield . By replacing the promoter, the production increased from 12% to five times as much . However, even under the same promoter, gene expression differed due to differences in translation rates .…”
Section: Introductionmentioning
confidence: 99%
“…By replacing the promoter, the production increased from 12% to five times as much [19,20]. However, even under the same promoter, gene expression differed due to differences in translation rates [21].…”
Section: Introductionmentioning
confidence: 99%